Mengeksplorasi Dampak Kekerasan dalam Rumah Tangga dan Pemerkosaan dalam Perkawinan di Indonesia - Puspita, Mega; Umami, Khairul (Institut Agama Islam Negeri Metro, 2024)
Domestic violence (DV) and marital rape are severe issues of ongoing concern in Indonesia. Domestic violence is defined as violence perpetrated by an individual who lives with the victim, while marital rape is an act of forced sexual intercourse by a husband against his wife without her consent. This research aims to explore the impact of domestic violence and marital rape on family integrity in Indonesia. The analysis was conducted through an in-depth literature review and case analysis between 2020 and 2023. The results show that factors such as patriarchal culture, power inequality in the household, lack of proper religious understanding, and socio-economic pressure are the leading causes of this violence. The impacts include physical and psychological harm to victims, the breakdown of family relationships, and a reduced quality of life in the community. This research emphasizes the importance of public education, legal reform, support for victims, and the active role of communities and religious institutions in preventing and addressing domestic violence and marital rape. With a holistic approach, it is hoped that domestic violence can be minimized to create a sakinah, mawaddah, and warahmah family.